2019
DOI: 10.1515/med-2019-0103
|View full text |Cite
|
Sign up to set email alerts
|

Application of exercised-based pre-rehabilitation in perioperative period of patients with gastric cancer

Abstract: AbstractObjectiveTo analyze the difference between exercised-based pre-rehabilitation and postoperative rapid rehabilitation of gastric cancer patients.MethodsThe clinical data of 120 patients who underwent surgical treatment between 2016 and 2018 in our hospital with pat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 24 publications
1
4
0
Order By: Relevance
“…52 In addition, preoperative rehabilitation (pre-rehabilitation) before upper abdominal surgery may help improve respiratory muscle strength. [53][54][55] We identified a poor OS in patients who underwent total gastrectomy, which is consistent with previous studies. [56][57][58] Fig.…”
Section: Discussionsupporting
confidence: 91%
“…52 In addition, preoperative rehabilitation (pre-rehabilitation) before upper abdominal surgery may help improve respiratory muscle strength. [53][54][55] We identified a poor OS in patients who underwent total gastrectomy, which is consistent with previous studies. [56][57][58] Fig.…”
Section: Discussionsupporting
confidence: 91%
“…2,[46][47][48][49][50][51][52][53] For the studies assessing periand postoperative physiotherapy, there were six RCTs [54][55][56][57][58][59] comparing an intervention with a control group, and one study 60 compared two different types of physiotherapy. Among the cohort studies, eight studies [61][62][63][64][65][66][67][68] S5. Finally, six RCTs 38,[40][41][42][43][44] and eight cohort studies 2,46-49,51-53 assessing prehabilitation, and five RCTs [54][55][56]58,59 and five cohort studies 61,62,65,67,68 S6 for each analysis.…”
Section: Literature Search Resultsmentioning
confidence: 99%
“…Among the cohort studies, eight studies [61][62][63][64][65][66][67][68] S5. Finally, six RCTs 38,[40][41][42][43][44] and eight cohort studies 2,46-49,51-53 assessing prehabilitation, and five RCTs [54][55][56]58,59 and five cohort studies 61,62,65,67,68 S6 for each analysis.…”
Section: Literature Search Resultsmentioning
confidence: 99%
“…Triple-modal pre-rehabilitation strategies consist of exercise, nutrition support, and psychological intervention. This strategy is useful for the preservation and recovery of organ function [11][12][13]. Several studies have reported that the use of triple-modal pre-rehabilitation strategies is more effective than the single pre-rehabilitation strategy [14,15].…”
Section: Introductionmentioning
confidence: 99%